Psychological predictors of the co-occurrence of problematic gaming, gambling, and social media use among adolescents. (March 2023) - Akbari, Mehdi; Bahadori, Mohammad Hossein; Khanbabaei, Salar; Milan, Bahman Boruki; Horvath, Zsolt; Griffiths, Mark D.; Demetrovics, Zsolt
Abstract: The aim of the present study was to explore which psychosocial predictors are associated with different co-occurrence patterns of three different behavioral addictions (i.e., problematic gaming, problematic social media use, and problematic gambling) among adolescents. A total of 2390 Iranian adolescents – 835 males and 1555 females aged between 13 and 18 years (M = 16.01 years, SD = 1.38) – participated in a cross-sectional online survey. Latent profile analysis produced four latent classes: a 'non-problematic behavior' class (N = 1766; 73.89% [Class 1]), a 'problematic gambling' class (N = 183; 7.66% [Class 2]), a 'problematic social media use with gaming disorder' class (N = 407; 17.03% [Class 3]), and a 'disordered gambling with problematic social media use' class (N = 34; 1.42% [Class 4]). Adolescent problem gamblers (Class 2) reported higher social support and lower self-esteem; adolescents with co-occurring problems for social media use and gaming (Class 3) had higher internalizing symptoms, higher sensation seeking and higher social anxiety; and adolescents with co-occurring problems of disordered gambling with problematic social media use (Class 4) had higher internalizing symptoms, lower social support and lower self-esteem. The 'non-problematic behavior' class (Class 1) had the lowest levels of internalizing psychopathological symptoms, loneliness, and social anxiety symptoms. Different psychological risk factors in the co-occurrence of problematic gambling, problematic social media use, and problematic gaming among adolescents were found that could help to identify adolescents who are vulnerable to more than one addictive behavior. More specialized prevention as well as treatment programs should be developed for these different types of addictive behavior. Highlights: Latent profile analysis produced four classes of co-occurrence patterns of problematic gaming, problematic social media use, and problematic gambling Adolescent problem gamblers reported higher social support and lower self-esteem Adolescents with co-occurring problems for social media use and gaming had higher internalizing symptoms, higher sensation seeking and higher social anxiety Adolescents with co-occurring problems of disordered gambling with problematic social media use had higher internalizing symptoms, lower social support and lower self-esteem